2019
DOI: 10.4103/jfmpc.jfmpc_462_18
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of disc herniation among general population in Aseer province, Saudi Arabia

Abstract: Background: Herniated lumbar disc is a depositions of discs material (nucleus pulposus and annulus fibrosus) behind the intervertebral disk. Intervertebral disc connected the vertebral bodies together by pad of fibrocartilage. The major functions of intervertebral disc are mechanical, transferring load coming from the body weight and muscle contractions by spinal columns and letting the curving, flexion, and contortion. Aim: To assess the awareness of general population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
(12 reference statements)
0
4
1
Order By: Relevance
“…2014). However, the results are different from the research conducted by Alshehri et al, (2019) which found that there was a male sex dominance in cases of lumbar disc herniation of 62.4% compared to women who were associated with physical activity and male work which tended to be heavier (Alshehri, A. K. et al, 2019).…”
Section: Discussioncontrasting
confidence: 77%
“…2014). However, the results are different from the research conducted by Alshehri et al, (2019) which found that there was a male sex dominance in cases of lumbar disc herniation of 62.4% compared to women who were associated with physical activity and male work which tended to be heavier (Alshehri, A. K. et al, 2019).…”
Section: Discussioncontrasting
confidence: 77%
“…Our study contrasts with a previous study which took place in Aseer, even though most of the participants have received higher education, the studied population revealed poor level of knowledge regarding the disease risk factors, preventive measures, and treatment. [ 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…The study participants showed poor awareness levels regarding all the aspects of disc herniation. [ 17 ]…”
Section: Introductionmentioning
confidence: 99%
“…Regarding marital status, the highest level of awareness was among single participants (35.3%), followed by divorced/widow (30%) and married (26.8%). However, previous studies demonstrated that married participants have a better knowledge level than single or divorced/widows(Murshid et al, 2020;Alshehri et al, 2019;Sahrah et al, 2016). In addition, 40.3% of participants who have attended or watched awareness about herniated disc have an excellent knowledge compared to 26.6% of those who have not.…”
mentioning
confidence: 90%
“…In a hospital-based study in Al Madinah Al Munawarah, the results showed they had good knowledge regarding LDH, as most of them had disc pathology and had been educated in the hospital (Murshid et al, 2020). On the other hand, in Aseer region, the awareness was very poor regarding disc prolapse, its risk factors, management and prevention (Alshehri et al, 2019).…”
Section: Valenzuela Et Al 2020)mentioning
confidence: 99%